THE CHOICE OF THE DRUG AMLODIPINE FOR THE HYPERTENSION TREATMENT FROM THE STANDPOINT OF ECONOMIC FEASIBILITY - S. Yu. Martsevich; N. A. Dmitrieva; A. D. Deev; Yu. V. Lukina; L. A. Sokolova; V. V. Yakusevich (Столичная издательская компания, 2016)
Aim. Тo compare the cost-effectiveness of antihypertensive therapy based on a generic and original drugs of amlodipine in patients with arterial hypertension (HT) degree 1-2 in NORST study. Material and methods. Patients (n=60) with HT degree 1-2 were involved in NORST study. After wash-out period they were randomized to receive generic (Group 1) or original (Group 2) amlodipine in the initial dose of 5 mg daily. In case of insufficient antihypertensive effect dose of amlodipine was increased to 10 mg per day and then successively lisinopril 10 mg daily and hydrochlorothiazide 12.5 mg one time per day were added. The total duration of treatment was 10 weeks (70 days). Achieving target blood pressure (BP) (<140/90 mm Hg) was the criterion of the effectiveness of therapy. Cost-effectiveness analysis of treatments in all patients was performed after individual analysis of the target BP achieving. Results. The target BP level was achieved in 25 (89%) patients of Group 1 and in 27 (96%) patients of Group 2. Total direct costs over 10 weeks amounted to 21 206 rubles in group 1, and 80 073 rubles in group 2. The cost-effectiveness ratio (CER) for group 1 was: CER=21 206/0.89=23 827 rubles. For Group 2, CER=80 073/0.96=83 409 rubles. Costs for achieving target BP in 1 patient of Group 1 were 3,5 times lower than these in group 2. Conclusion. The use of generic amlodipine (Stamlo M) has opportunity to draw in the healing process more hypertensive patients due to reducing the cost of treatment.